KUALITAS LAYANAN PENDAFTARAN CALON JAMAAH HAJI PADA KANTOR KEMENTERIAN AGAMA KABUPATEN HULU SUNGAI UTARA - Riduan, Akhmad (PPPM STIA Amuntai, 2020)
Hajj is the fifth pillar of Islam, and as mandated by the Law of the Republic of Indonesia Number 8 of 2019 concerning the Implementation of Hajj and Umrah, the government is fully involved in the implementation of the haj which includes guidance, services and protection for pilgrims, from the registration process to departure, services during the pilgrimage season until returning to their respective regions. For the purposes of this research, a descriptive-qualitative research method was used with a number of key informants by purposive sampling. The data collected through the technique of observation, interviews, and documentation were analyzed by data reduction, data display, and conclusion drawing / verification. Based on the results of the research, from the aspect of tangible, it is known that the facilities and infrastructure in the Hajj and Umrah Implementation Section (PHU) are still not good because the waiting room is narrow, there is no television provision and some of the registration service equipment is damaged. Employee discipline is still not good and there is a lack of awareness from employees, but the appearance of employees is good where they are already wearing uniforms according to existing regulations. Next, from the aspect of reliability, it is known that the accuracy of PHU Section employees at the stages of receiving and checking the data for the Hajj Candidates (CJH) concerned is good, but in terms of implementing the Standard Operating Procedure (SOP), some employees have not fully implemented it. Then from the aspect of responsiveness it is known that the readiness of employees in the PHU Section in serving CJH is still not good, namely at the stage of receiving the validation number where they have not been responsive in providing information about the validity period of the validation number to CJH but the response to service users is relatively fast and a suggestion box is available for respond to complaints. Furthermore, from the aspect of assurance, it is known that the timeliness of service is still not good, such as inputting CJH's biodata into the SISKOHAT application, printing SPPH and the Portion Number of the SISKOHAT application to be signed by CJH and Kasi PHU which are still not in accordance with existing SOPs but related to service costs In the service, there is no fee other than the fees stipulated in the SOP, namely CJH pays the initial deposit of Hajj Administration Fee (BPIH) of 25 million at the Deposit Recipient Bank (BPS). As for the aspect of empathy, the attitude of the PHU Section employees in service is not discriminatory and services are carried out with good courtesy.To improve the quality of CJH registration services in Hulu Sungai Utara Regency, it is hoped that the Head of Ministry of Religion office will seek to expand the waiting room in the PHU Section, equip facilities and infrastructure that are lacking/damaged, and provide guidance to undisciplined employees. PHU Section employees should carry out maintenance of work facilities on a regular basis, increase discipline, always motivate themselves to support the CJH registration services in addition to being responsive in informing CJH conventionally via announcement boards or online. CJHs should be able to be involved in socialization activities carried out by the PHU Section.